The Middle Class in the Philippines : An Exploration of the Conditions for Upward Mobility - World Bank (World Bank, Washington, DC, 2020)
A decade of rapid economic growth has supported upward mobility and the expansion of the middle class in the Philippines. While the Philippines’ record of economic growth has been sound, many East Asian countries have performed better, resulting in higher levels of economic mobility and more rapid middle-class expansion. This study aims to inform these efforts through an in-depth examination of varying factors that affect upward mobility and middle-class expansion in the Philippines.